SOSIALISASI PEMANFAATAN EKSTRAK CHAMOMILE (Matricaria Chamomilla L) SEBAGAI MUSCLE RELAXANT PADA FORMULASI ROLL ON AROMATERAPI - Erika Cantika; Dea Ananda Amelia; Muhammad Kahfi Iswanto Putra; Putri Apriliana; Zihni Mahira Rahman; Qisti Cahya Putri Ramdani; Leisya Fauzia Ramadinda (Jurnal Pengabdian IKIFA, 2024)
Myalgia is a term for muscle pain. Myalgia originates from Greek, where "myo" means muscle and "algos" means pain. Muscle pain is a common ailment among the general public. The symptoms and location of muscle pain vary from person to person, depending on the activity and the cause of the muscle pain itself. The prevalence of myalgia ranges from 50-62% of the total population worldwide. In Indonesia, the prevalence of myalgia sufferers ranges from 45-59%. Myalgia arises from excessive muscle activity. This can be reduced by substituting chemicals with natural ingredients, one of which is the Chamomile plant. Chamomile is known as an herbal remedy for treating diseases. The Chamomile plant contains apigenin, which functions like benzodiazepine, providing a hypnotic effect by binding to GABA A receptors in the central nervous system, thereby inducing a sedative effect and causing muscle relaxation. The aromatherapy roll-on is made by measuring the ingredients according to the formula. This community service activity was carried out at SMK PGRI 2 Cimahi, with 21 students participating. The results of the counseling activities were beneficial in increasing the students' knowledge.